Selling Weimar : German Public Diplomacy and the United States, 1918–1933 (Volume 60) - Piller, Elisabeth (Franz Steiner Verlag, 2020)
In the decade after World War I, German-American relations improved swiftly. While resentment and bitterness ran high on both sides in 1919, Weimar Germany and the United States managed to forge a strong transatlantic partnership by 1929. But how did Weimar Germany overcome its post-war isolation so rapidly? How did it regain the trust of its former adversary? And how did it secure U.S. support for the revision of the Versailles Treaty? Elisabeth Piller, winner of the Franz Steiner Preis für Transatlantische Geschichte 2019, explores these questions not from an economic, but from a cultural perspective. Based on extensive archival research, her ground-breaking work illustrates how German state and non-state actors drew heavily on cultural ties – with German Americans, U.S. universities and American tourists – to rewin American trust, and even affection, at a time when traditional foreign policy tools had failed to achieve similar successes. Contrary to common assumptions, Weimar Germany was never incapable of selling itself abroad. In fact, it pursued an innovative public diplomacy campaign to not only normalize relations with the powerful United States, but to build a politically advantageous transatlantic friendship. "In her deeply researched, vividly illustrated history of cultural-diplomatic relations between Weimar Germany and the United States, Elisabeth Piller charts a new course in the history of transatlantic interwar diplomacy." Victoria de Grazia, Columbia University "This is a splendidly written and researched work of history, crossing any number of geographic and cultural borders. With much transatlantic verve, Dr. Piller has achieved a masterful synthesis of diplomatic, intellectual and cultural history." Michael Kimmage, Catholic University of America